Application of ultrathin TiO2 layers in solar energy conversion devices. Issue 5 (31st March 2022) - Zhou, Chenyu; Xi, Zhaoyi; Stacchiola, Dario J.; Liu, Mingzhao
Abstract: A vital pursuit in solar energy research is to achieve high efficiency and long‐term stability in energy conversion devices. Coating or sandwiching an ultrathin layer of TiO2 onto active solar components has been demonstrated to be a remarkably effective and facile strategy to improve their stability. The TiO2 film acts as a protection layer and enhances solar energy conversion efficiency by passivating surface recombination sites or facilitating electron transport. To date, numerous efforts have been devoted to applying ultrathin TiO2 layers in various kinds of solar energy conversion devices. In this study, we review deposition techniques, characterization methods of the resulting ultrathin TiO2 layer, as well as its applications in dye‐sensitized solar cells, organic–inorganic hybrid solar cells, and photoelectrochemical cells. Abstract : In this study, we review deposition techniques, characterization methods of the resulting ultrathin TiO2 layer, as well as its applications in dye‐sensitized solar cells, organic–inorganic hybrid solar cells, and photoelectrochemical cells.